Spatial and temporal variability of chlorophyll concentrations from nimbus-7 coastal zone colour scanner data in the Benguala upwelling system and the sub-tropical convergence region south of Africa - Weeks, Scarla Jeanne (Department of Oceanography, 2016)
Bibliography: pages 68-74.